A role for CCR5+CD4 T cells in cutaneous psoriasis and for CD103+ CCR4+ CD8 Teff cells in the associated systemic inflammation. (June 2016) - Sgambelluri, Francesco; Diani, Marco; Altomare, Andrea; Frigerio, Elena; Drago, Lorenzo; Granucci, Francesca; Banfi, Giuseppe; Altomare, Gianfranco; Reali, Eva
Abstract: Recent results have identified critical components of the T cell response involved in the initiation and amplification phases of psoriasis. However the link between T cell responses arising in the skin and the systemic inflammation associated with severe psoriasis is largely unknown. We hypothesized that specific subsets of memory T cells recirculating from the skin could play a role. We therefore dissected the circulating memory T cell compartment in patients by analyzing the TCM, TEM and Teff phenotype, the pattern of CCR4 and CCR5 chemokine receptor expression and the expression of the tissue homing molecule CD103. For each subset we calculated the correlation with the Psoriasis Area and Severity Index (PASI) and with the extent of systemic inflammation measured as serum level of the prototypic short pentraxin, C reactive protein (CRP). Validation was performed by comparison with gene expression data in psoriatic plaques. We found that circulating CD103 + CCR4 + CCR5 + and CCR4 + CCR6 - CD8 + Teff cells, were highly correlated with CRP levels as well as with the validated index PASI, reflecting a link between skin involvement and systemic inflammation in patients with severe psoriasis. In addition we observed a contraction of circulating CCR5 + T cells in psoriasis patients, with a highly significant inverse correlation between CCR5 + CD4 T cells and the PASI score. Increased expression of CCR5 and CCL5 genes in psoriatic skin lesions was consistent with an accumulation of CCR5 + cells in psoriatic plaques indicating a role for CCR5/CCL5 axis in disease pathogenesis. Highlights: The link between T cell responses arising in the skin and systemic inflammation associated with severe psoriasis is unknown. Specific subsets of memory T cells recirculating from the skin could play a role. Contraction of circulating CCR5 + T cells in psoriasis patients and inverse correlation between CCR5 + CD4 T cells and PASI. Increased expression of CCR5 and CCL5 genes in psoriatic plaques indicates a role of CCR5/CCL5 axis in disease pathogenesis. Circulating Teff fraction of CD103 + CCR4 + CD8 + T cells correlates with both systemic inflammation and cutaneous manifestations.